The inhibitors of miR-224-5p, miR-339-5p, and miR-1198-5p improve auditory function by promoting the expression of neuritin in hearing loss mice - Pingping Meng; Zhiwei Zhong; Yin Song; Yu Wei; Jiawei Sun; Jingyi Chen; Yunhua Zhang; Jingling Zhu (PLoS ONE, 2026)
Background Sensorineural hearing loss (SNHL) is the main type of hearing impairment, and currently there is a lack of effective preventive or therapeutic drugs. Our previous research revealed that the expression of neurotrophic factor Neuritin decreased in hearing loss. After treatment with recombinant human Neuritin protein, the number of hair cells significantly increased. However, the molecular mechanism underlying the decreased expression of Neuritin in hearing loss remains unclear. Research indicates that Neuritin expression is regulated by microRNAs (miRNAs). This study aims to screen and validate the key miRNAs that regulate the expression of Neuritin and assess the feasibility of these miRNAs as therapeutic targets for SNHL. Methods This study utilized a mouse model of SNHL and employed high-throughput sequencing and bioinformatics analysis to screen for miRNAs that regulate the expression of neurofilament proteins in cochlear tissues. Subsequently, in vivo experiments were conducted to verify the regulatory effects of the candidate miRNAs on neurofilament proteins and to evaluate the improvement of SNHL by the corresponding miRNA inhibitors. Results After screening and identification, three miRNAs specifically inhibiting the expression of neurofilament protein were obtained, namely miR-224-5p, miR-339-5p and miR-1198-5p. The in vivo experimental results indicated that the inhibitors of the above three miRNAs had a significant improvement effect on the SNHL mouse model. Conclusion MiR-224-5p, miR-339-5p and miR-1198-5p can be involved in the pathogenesis of SNHL by regulating the expression of neurofilament proteins. Targeting these miRNAs or their inhibitors can provide new molecular targets and strategies for the prevention and treatment of SNHL.